Light driven isomerization of coordinated ligand and modulation of fac-[Re(CO)3(phen)(trans-bpe)]PF6 photoluminescence in rigid media - Melina Kayoko Itokazu; André Sarto Polo; Neyde Yukie Murakami Iha (International Journal of Photoenergy)
The excited state reactivity and photophysical properties of fac-[Re(CO)3(phen)(L)]PF6 (phen = 1,10-phenanthroline, L = trans- or cis-1,2-bis(4-pyridyl)ethylene, bpe) in PMMA (poly(methyl methacrylate)) films have been investigated and compared with those in acetonitrile solution.